2023
DOI: 10.1001/jama.2023.24491
|View full text |Cite
|
Sign up to set email alerts
|

Prone Positioning During Extracorporeal Membrane Oxygenation in Patients With Severe ARDS

Matthieu Schmidt,
David Hajage,
Guillaume Lebreton
et al.

Abstract: ImportanceProne positioning may improve outcomes in patients with severe acute respiratory distress syndrome (ARDS), but it is unknown whether prone positioning improves clinical outcomes among patients with ARDS who are undergoing venovenous extracorporeal membrane oxygenation (VV-ECMO) compared with supine positioning.ObjectiveTo test whether prone positioning vs supine positioning decreases the time to successful ECMO weaning in patients with severe ARDS supported by VV-ECMO.Design, Setting, and Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…For patients indicated for VV-ECMO, the 90-day survival rate of 62.1% of our cohort is consistent with large studies and registries [15,16], and it is slightly higher than the rate reported in a recent randomized controlled study assessing the continuation of the prone position during VV-ECMO [17].…”
Section: Discussionsupporting
confidence: 91%
“…For patients indicated for VV-ECMO, the 90-day survival rate of 62.1% of our cohort is consistent with large studies and registries [15,16], and it is slightly higher than the rate reported in a recent randomized controlled study assessing the continuation of the prone position during VV-ECMO [17].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the relationship between PP and ECMO duration requires further investigation. Recent study on this aspect found that prone positioning did not significantly reduce time to successful weaning of ECMO ( 21 ). Our subgroup analysis was consistent with it.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with ARDS has improved in recent years due to increased awareness and effective supportive therapy [ 1 , 2 ]. However, ARDS-related mortality remains unacceptably high, as shown by a recent study in which the 60-day mortality was up to 44.1% among those with severe ARDS [ 3 ]. Currently, effective treatments for ARDS are still lacking, and ARDS remains one of the major public health burdens worldwide.…”
Section: Introductionmentioning
confidence: 99%